Behaviours of wild male and female Colobus angolensis palliatus during morning and afternoon in Diani Beach, Kenya - Buskas, Julia (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
Colobus angolensis palliatus is a small old world monkey inhabiting southern coastal Kenya to southern Tanzania. The species activity budget is known to vary between seasons and areas, probably due to differences in group sizes, diets, predatory presence and resource competition. The variations between male and female activity budgets are reckoned to be a result of pregnancy and lactation. The aim of this study was to investigate potential differences in behaviours between morning and afternoon periods and between males and females. The study was carried out in two forest fragments in Diani Beach on the south coast of Kenya. A total of four groups of C. a. palliatus were observed during an eight day survey, divided into morning and afternoon observation periods. The method used during the recordings was focal sampling with instantaneous recording. The results indicate differences in proportions of observations spent on behaviours between morning and afternoon periods. The variations in the behaviours feeding (27.0 vs 48.6 %; P < 0.001), resting (59.1 vs 39.7 %; P < 0.001) and auto grooming (3.8 vs 2.5 %; P = 0.018) may be due to ambient temperature, predatory avoidance, competition over resources or season and area. There were no differences in social behaviours and moving between morning and afternoon. There were no differences in the proportion of observations spent on feeding, resting, auto grooming, moving and other behaviours between males and females. However, females spent more time with social behaviours compared to males (2.0 vs 0.4 %; P = 0.009), probably due to more allo grooming among females.